ANALISIS DAMPAK PENDEMI COVID-19 TERHADAP TINGKAT DAYA BELI MASYARAKAT DAN PENDAPATAN UMKM DI DISTRIK MERAUKE - marthen ai nahumury; Brigta Brigta brigta (Musamus Journal of Economics Development, 2024)
Covid-19 is a vulnerable situation that threatens many problems in various parts of the world. Not only does it interfere with public health problems but also has the effect of various policy actions taken by the government in overcoming the Covid-19 problem. The economy of the State, Region, even to remote rural areas has experienced a drastic decline and caused a lot of social degradation which has triggered social problems in various areas where crime has taken place everywhere. The level of people's purchasing power has decreased due to the influence of the income of the population has decreased. The purpose of this study was to find out how much influence Covid-19 had on the income and purchasing power of the people in the Merauke District. This type of research is exploratory descriptive qualitative in the form of research using the case method approach in the Merauke District. The results of this study indicate that when conducting research in the field, the influence of Covid-19 is very large and has an impact on society, thus triggering a decrease in purchasing power. Keywords: Covid-19, Income, Purchasing Power Level.